Water‐Resistant Organic Room‐Temperature Phosphorescence from Block Copolymers - Chen, Huan; Zhang, Yuanyuan; Shan, Jingyi; Dong, Mengyang; Qian, Zhao; Lv, Anqi; Qian, Hu‐Jun; Ma, Huili; An, Zhongfu; Gu, Long; Huang, Wei (Angewandte Chemie International Edition, 2025)
Room‐temperature phosphorescence (RTP) polymers have demonstrated significant potential for various applications due to their unique luminescent properties. However, most conventional RTP polymers are vulnerable to moisture and water, which can disrupt the hydrogen bonding network within the polymer and accelerate the non‐radiative decay of triplet excitons of phosphors, leading to the quenching of RTP. Herein, we present a universal strategy to achieve water‐resistant RTP polymers by designing amphiphilic block copolymers with microphase‐separated structures. Specifically, the rigid hydrophilic phase, which is rich in carboxyl groups, forms hydrogen bonds that suppress non‐radiative decay of the chromophores, resulting in RTP. Meanwhile, the hydrophobic phase effectively prevents water molecules from penetrating and disrupting the rigid polymer network. By combining the functions of both the hydrophilic and hydrophobic phases, the resulting RTP copolymers exhibit good water‐resistant properties. Even after being immersed in water for one month, the copolymers maintain a green afterglow with a lifetime of 629 ms. Moreover, the water‐resistant nature of these RTP polymers has also been demonstrated in potential applications of afterglow displays and anti‐counterfeiting. This research offers valuable insights into the design of RTP materials with stability in aqueous environments and broadens the scope of their potential applications in diverse settings. Water‐resistant organic room‐temperature phosphorescence materials are achieved by fabricating the microphase separation structure in block copolymers via synergizing the hydrophilic and hydrophobic phases. After the self‐assembly, the hydrophilic blocks were surrounded by hydrophobic blocks to mitigate water ingress. The resulting copolymers exhibit a long phosphorescent lifetime and decent water‐resistant properties, demonstrating potential applications in afterglow display and information encryption.